American sniper : the autobiography of SEAL Chris Kyle, (USN 1999-2009), the most lethal sniper in U.S. military history /: the autobiography of SEAL Chris Kyle, (USN 1999-2009), the most lethal sniper in U.S. military history. (2012) - Unknown
No abstract available